The association between Long-COVID symptomology, perceived symptom burden and mental health in COVID-19 patients in Shijiazhuang, China: a population-based health survey - Li, Yufei; Lam, Lawrence T.; Xiao, Ying; Qiu, Zhengqi; Zhang, Yanming (Frontiers in Psychiatry, 2024)
Background: Long-COVID (LC) refers to post-acute COVID-19 symptoms that can last for months or longer after the initial infection, affecting the physical health of infected patients. This study aims to investigate the association between the symptomology of LC and the mental health of patients in China. It also aims to examine the relationship between the perceived symptom burden and mental health of these patients.Methods: A population-based stratified cluster sample was recruited, using a standard sampling procedure, from a prefecture-level city in Northern China.Participants included patients who had tested positive for COVID-19 after December 2022. LC symptomology was assessed using a LC symptoms checklist where the perceived symptom burden was measured by the included 5-point Likert scales. Mental health of patients was measured using the Depression, Anxiety, and Stress Scale (DASS), the original Connor-Davidson Resilience Scale (CD-RISC), and the Duke-UNC Functional Social Support Questionnaire (DUFSS). Data were analysed using multiple linear regression models.Results: About 25% of respondents, experienced COVID symptoms lasting longer than two months that could only be explained by the infection. Post-exertional malaise (22.2%) and fatigue (21.2%) were the most common symptoms. After controlling for potential confounding variables, LC symptomology was significantly and positively associated with depression (t=2.09, p=0.037) and anxiety (t=4.51, p<0.001), but not stress. Perceived symptoms burden was also positively and significantly related to depression (β=0.35, p<0.001), anxiety (β=0.54, p<0.001), and stress (β=0.35, p<0.001), suggesting a dose-response relationship between perceived symptom burden and mental ill health.Conclusions: This study highlights the importance of recognizing the risk of LC, patients’ perception of the symptom burden and its potential impact on mental health. Healthcare professionals should be aware of the complexity of psychological comorbidities among infected patients reporting prolonged symptoms, and be able to give advice regarding long-term management of the symptoms.